Priced out : Stuyvesant Town and the loss of middle-class neighborhoods - Woldoff, Rachael; Morrison, Lisa M.; Glass, Michael R. (New York University Press, 2016)
On an average morning in the tree-lined parks, plazas, and play-areas of Manhattan's Stuyvesant Town housing development, birds chirp as early risers dash off to work, elderly residents enjoy a peaceful morning stroll, and flocks of parents usher their children to school. It seems an unlikely location for conflict and strife, yet this eighteen-block area, initially planned as middle-class affordable housing, is the site of an ongoing struggle between long-term, rent-regulated residents, younger, market-rate tenants, and new owners seeking to turn this community into a luxury commodity. 'Priced Out' takes readers into this heated battle as a transitioning neighborhood wrestles with contemporary capitalist strategies and the struggle to preserve renters' rights.